Cardiovascular Risk Assessment among Adults in Primary Health Care Settings in Sulaimani Using WHO Risk Prediction Charts - Najim Edeen, Vian; Salah Ramzi, Zhian (Kurdistan Journal of Applied Research, 2018)
WHO adopted World Health Organization/International Society of Hypertension (WHO/ISH) risk charts to predict cardiovascular disease risk in low and middle income countries. The aim of this study was to estimate the cardiovascular risk in adults ?40 years old by using the two versions of the WHO/ISH risk prediction charts “with and without cholesterol”, and to find out the risk by other parameters not found in the chart; also, to evaluate concordance between the two approaches. A cross-sectional study was conducted from August 2016 to February 2017 in two primary health care centers in Sulaimani City among 500 persons aged 40-82 years. The desired information was collected by using a pretested questionnaire; anthropometric measurements and laboratory investigations were also carried out for the participants. Cardiovascular risk was assessed by the WHO/ISH risk prediction charts for the Eastern Mediterranean region in category D. Mean age of the participants was 52.5(±9.55) years and 70.4% of the participants were females. Only 260 participants had the results of total cholesterol and triglycerides. The results revealed that, using the risk assessment charts with and without cholesterol, 22.3% and 19.2% respectively of the study population were in the ten-year cardiovascular risk category of ?20%. Risk categories were concordant in 86.2% of the population; and when we applied single risk factor approach 51.5% would require drug treatment. The WHO/ISH risk chart is an affordable and simple tool to estimate cardiovascular disease risk. Nearly one fifth of adults aged ? 40 years in Sulaimani City are at high-very high risk of developing cardiovascular event in the next ten years as assessed by WHO/ISH risk prediction charts. The use of the without cholesterol version of the chart to estimate cardiovascular disease risk could be useful is settings where cholesterol cannot be measured.